Desain Dalam Kriya Seni Dan Industri Kerajinan - Agus Ahmadi (Ornamen, 2008)
An effort of developing design is required in the attempt of improving the quality of craft product, determining the beauty value and proper function as well as increasing production, thereby improving the competitiveness to reach a wider market. In order to design and art craft work, design picture should be manifested clearly according to the projection shape/picture, perspective picture, ornamental motive applied, measurement in the correct scale, and the material as well as equipment limitation and finishing should be taken into consideration.The art craft is the product of work prioritizing the hand skill with certain technique that is presented beautifully and interestingly so that it will give or generate the inner experience to other human beings who enjoy it.Design development in improving the quality and production capability of craft work can be conducted to one or several elements of it: material change, working process upgrading, new equipment usage, finishing process development, package improvement, function element replacement and marketing channel upgrading.Keywords: design, craft, industry and development